The stability of an inhomogeneous rational integrator for the solution in ordinary differential equations - Ebhohimen*†, F.; Akhanolu†‡, G.A. (International Journal of Mathematical Analysis and Modelling, 2023)
This research work is concerned with the determination of solution to different classes of problems in Ordinary Differential Equations (ODEs). We derived an inhomogeneous rational integrators for the solution of ordinary differential equations. The convergence and consistency and scheme in the interpolant of order m = 4, was established. The stability function and the analysis of the method was carried out with the use of MAPLE-18 and MATLAB software. We compared our new integrator with some recent existing methods and discovered that ours compete favorably well with a very high rate of convergence..Our result shows that the new integrator is stable analytically and computationally.